INVESTIGATING THE EFFECT OF STRUCTURAL PARAMETERS OF THE MESH SURFACE ON CLEANING EFFICIENCY IN MECHANICAL COTTON SEED CLEANING UNITS (World Conference on Agricultural and Earth Sciences, 2026)
The article presents the results of experimental studies carried out on both the existing and improved Mechanical seed (cotton seed) cleaning cleaners installed in the Cotton seed sorting unit unit, aimed at increasing the cleaning efficiency of cotton seeds.
Keywords: cleaning, sorting, agregat (unit), efficiency, , regulation cotton seeds, impurity.